The miniJPAS survey - optical detection of galaxy clusters with PZWav - Doubrawa, Lia; Cypriano, E. S.; Finoguenov, A.; Lopes, P. a. A.; Gonzalez, A. H.; Maturi, Matteo; Dupke, R. A.; Delgado, R. M. González; Abramo, R.; Benitez, N.; Bonoli, S.; Carneiro, S.; et al. (Astronomy and astrophysics, 2024)
Context. Galaxy clusters are an essential tool to understand and constrain the cosmological parameters of our universe. Thanks to its multi-band design, J-PAS offers a unique group and cluster detection window using precise photometric redshifts and sufficient depths. Aims. We produced galaxy cluster catalogues from miniJPAS, which is a pathfinder survey for the wider J-PAS survey, using the PZWav algorithm. Methods. Relying only on photometric information, we provide optical mass tracers for the identified clusters, including richness, optical luminosity, and stellar mass. By reanalysing the Chandra mosaic of the AEGIS field, alongside the overlapping XMM-Newton observations, we produced an X-ray catalogue. Results. The analysis revealed the possible presence of structures with masses of 4 × 10 13 M⊙ at redshift 0.75, highlighting the depth of the survey. Comparing results with those from two other cluster catalogues provided by AMICO and VT, we found 43 common clusters with cluster centre offsets of 100 ± 60 kpc and redshift differences below 0.001. We provide a comparison of the cluster catalogues with a catalogue of massive galaxies and report on the significance of cluster selection. In general, we were able to recover approximately 75% of the galaxies with M⋆ > 2 × 10 11 M⊙. Conclusions. This study emphasises the potential of the J-PAS survey and the employed techniques, including down to group scales.